Pembiayaan Pendidikan Islam; Historis, Pengertian, Fungsi, dan Sumber - Ahmad Firdaus Al amien; Siti Julaiha; Muhammad Adam Dzuhri (CV. Syntax Corporation Indonesia, 2021)
Understanding the basic concepts of Islamic education financing is very important, because it is known that Islamic education financing has undergone various developments and the role of financing has a very large influence on the educational process. Therefore, this study aims to describe the basic concepts of Islamic education financing, so that readers can find out the origin, definition, function and source of Islamic education financing which are systematically described in this study. The method used in this study is a qualitative research with a library research approach to describe the contents of the article. The results of this study focus on the aspect of the function of the article which will make it easier for academics to find references that discuss the basic concepts of financing Islamic education